2022
DOI: 10.1002/rcm.9370
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in measuring nitrogen isotope signatures in inorganic nitrogen forms: An interlaboratory comparison of three common measurement approaches

Abstract: Rationale Stable isotope approaches are increasingly applied to better understand the cycling of inorganic nitrogen (Ni) forms, key limiting nutrients in terrestrial and aquatic ecosystems. A systematic comparison of the accuracy and precision of the most commonly used methods to analyze δ15N in NO3− and NH4+ and interlaboratory comparison tests to evaluate the comparability of isotope results between laboratories are, however, still lacking. Methods Here, we conducted an interlaboratory comparison involving 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…All studies employing 15 N as a tool are depending on accurate and precise determination of the stable isotope ratio in environmental samples. Many methods exist for analyzing the 15 N abundance of inorganic N species (ammonium and nitrate) in liquid samples (Biasi et al 2022), all with their own limitations and advantages. Jia et al (2022) conducted an extensive literature review on those methodologies as a base for developing a decision support tool as a guideline for research to select appropriate analysis methods for their samples.…”
Section: Methodological Advancesmentioning
confidence: 99%
“…All studies employing 15 N as a tool are depending on accurate and precise determination of the stable isotope ratio in environmental samples. Many methods exist for analyzing the 15 N abundance of inorganic N species (ammonium and nitrate) in liquid samples (Biasi et al 2022), all with their own limitations and advantages. Jia et al (2022) conducted an extensive literature review on those methodologies as a base for developing a decision support tool as a guideline for research to select appropriate analysis methods for their samples.…”
Section: Methodological Advancesmentioning
confidence: 99%
“…This difference in performance likely has two reasons: first, a higher background in 28 N 2 , 29 N 2 , and 30 N 2 due to the requirement for a more complex setup with additional connectors (e.g., selector valve, Nafion dryer, ascarite trap); second, the 3N-SPIN-MIMS system uses helium as a carrier gas, which dilutes the analytes, while as established by Eschenbach et al, the analytes diffused directly into the high-vacuum of the QMS. The NH 4 + conversion to N 2 O via NO 2 – or NO 3 – offers potential to improve sensitivity, but was not implemented and tested due to the higher complexity and the extended reaction times, which might impede online conversion …”
Section: Methodsmentioning
confidence: 99%
“…This difference in performance likely has two reasons: first, a higher background in 28 N 2 , 29 N 2 , and 30 N 2 due to the requirement for a more complex setup with additional connectors (e.g., selector valve, Nafion dryer, − offers potential to improve sensitivity, but was not implemented and tested due to the higher complexity and the extended reaction times, which might impede online conversion. 34 2.1.4.3. Accuracy and Precision for 15 .…”
Section: Limits Of Detection (Lods) and Limits Of Quantification (Loqs)mentioning
confidence: 99%
“…17 However, it has been reported that high variability of the nitrogen isotope results have been produced by the denitrifier method by conducting an interlaboratory comparison of denitrifier methods and other methods on standards and environmental samples. 24 And one of the potential reasons which caused the big variability is that the measured results needed to be corrected by the nitrogen isotope calibration. Therefore, the standard calibration method to correct the measurement results of nitrogen isotopes should be used with caution.…”
Section: Introductionmentioning
confidence: 99%